Analysis of the effectiveness of project-based learning in social studies learning to foster empathy and environmental awareness in elementary school students - Ayu Erisha Putri, Ni Putu; Widi Artini, Komang Ayu; Susiani, Ketut (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This research aims to apply the Project Based Learning (PjBL) learning model in Social Sciences (IPS) subjects at the elementary school level as an effort to increase students' empathy and environmental awareness to support the achievement of Sustainable Development Goals (SDGs) 13 related to action on climate change. This study was conducted using a literature review approach that included various scientific articles and relevant academic sources. The results of the study show that the PjBL model is effective in increasing student active participation, building concern for the environment, and developing social empathy. Through contextual projects related to environmental issues, students not only understand social studies concepts in a more meaningful way, but also internalize character values that support sustainable development. These findings reinforce the importance of integrating project-based learning approaches in social studies curricula to develop a generation that is environmentally conscious and globally competitive